2 - Critical Reflections on the Joint Africa-EU Strategy - Ölund Maria (Africa Development, 2021)
The Joint Africa-EU Strategy (JAES), adopted at the EU-Africa Lisbon Summit in 2007, is a vision for a long-term relationship between Africa and Europe in which the two should come together in a shared framework for stronger collaboration. I will here critically reflect on the JAES based on developments up to the recent high-level Africa Europe meeting which took place in Tripoli in December 2010. The developments are well documented and debated both on an official level and by the NGO community. The article is based on a literature review. The findings point at some positive developments, but also on many and difficult challenges met. The historical heritage is very difficult to overcome, but is also a starting point for better and more equal relationships in the future. Very little seems to have been done to meet the new challenges from new actors on the scene and the increased strength of many African countries due to raw- material shortages in the rest of the world and improved economic developments. However, success in implementing the JEAS will, in the final analysis, depend on how well the strategy will be owned by the countries and peoples of Africa and Europe.